L'administration provinciale sous l' ancien empire égyptien - Martinet, Émilie, (Probleme der Ägyptologie;, 2019)
In L'Administration provinciale sous l'Ancien Empire égyptien, Émilie Martinet offers an innovative analysis of the provincial administrative structures and the stratification of the local elites in the Old Kingdom (2700-2160 BC) based on a critical study of sources and building on a database containing about 1500 titled individuals. She applies a comprehensive and novel approach which goes beyond the scope of prosopographical analysis and which includes all the hierarchy levels as well as the links between central administration and provincial administration. The exhaustive character of this study, the historical reasoning which is employed, and the development of a typology of provincial administrative structures and of a new terminology for the rulers of the provinces are among the major assets of this book.